A Health Technology Assessment of the Strokefinder MD100 For Early Detection of Stroke and Traumatic Brain Injury in the Western Cape Healthcare System, South Africa - Alvaeus Tynnerstål, Ebba; Thornander, Alice (My University, 2025)
Stroke is the second leading cause of death worldwide, with particularly high prevalence in low- and middle-income countries (LMIC) such as South Africa. Traumatic Brain Injury (TBI) accounts for approximately six million deaths annually and is commonly caused by trauma, an especially significant issue in South Africa (SA), where rates of interpersonal violence and traffic accidents are notably high. The South African healthcare system consists of a private and a public sector. The private sector are profit-driven hospital groups, while the public sector is governmentfunded. The public system operates on a referral-based model, which is not wellsuited to managing time-sensitive medical conditions such as stroke and TBI. This report presents a Health Technology Assessment (HTA) of the Strokefinder MD100 device developed by the Swedish company Medfield Diagnostics AB, within the context of the healthcare system in the Western Cape, South Africa. The HTA is based on an extensive literature review combined with semi-structured qualitative interviews conducted with relevant stakeholders. The findings support the final recommendations for optimal implementation sites of the MD100 with the main purpose of minimising time-to-treatment and thereby improve patient outcomes. With the identified healthcare needs in the Western Cape, the most appropriate implementation sites are identified to be in pre-hospital units, within both private and public healthcare sectors, or in level 1 hospital facilities lacking CT imaging capabilities within the public healthcare sector.
Keywords: Strokefinder MD100; HTA; Assessment; Western Cape South Africa; Triage; TBI; Medfield Diagnostics; Stoke; Truma; Healthcare